2012
DOI: 10.2298/pac1201021g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Fe-doped TiO2 powders for solar light response and photocatalytic applications

Abstract: Different amounts of Fe-doped TiO2 (with 0.1 to 10 wt.% Fe) powders were prepared at temperatures in the range of 400 and 800?C following a conventional co-precipitation technique and were thoroughly characterized by means of X-ray diffraction (XRD), Fourier-transform infrared (FT-IR), Fourier-transform Raman (FT-Raman), diffuse reflectance spectroscopy (DRS), BET surface area, zeta potential and flat band potential measurements. Photocatalytic ability of Fe-doped TiO2 powders was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
64
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 39 publications
(1 reference statement)
13
64
4
3
Order By: Relevance
“…Therefore, in these nanopowders the rutile structures are dominant compared to the anatase structures in terms of their intensity. These results are quite different compared to the previous studies, where they were observed the transformation phase structures from rutile crystal structure to anatase crystal structure after annealing at 800 o C [8]. Also, another previous study showed that TiO2:Fe was in rutile structures.…”
Section: Resultscontrasting
confidence: 91%
“…Therefore, in these nanopowders the rutile structures are dominant compared to the anatase structures in terms of their intensity. These results are quite different compared to the previous studies, where they were observed the transformation phase structures from rutile crystal structure to anatase crystal structure after annealing at 800 o C [8]. Also, another previous study showed that TiO2:Fe was in rutile structures.…”
Section: Resultscontrasting
confidence: 91%
“…FT-IR spectra reveal some weak transmittance bands between 1020 to 1650 cm -1 and 2800 to 3500 cm -1 and it also shows a gradual decrease in peak intensities with increasing Fe concentration. These bands are attributed to the stretching vibration of O-H groups and bending vibration of absorbed water molecules [6]. Further, the bands Between 500 to 830 cm -1 may be due to different vibrational modes of TiO 2 , the broad intense band at 1200 cm -1 may be due to Ti-O-Ti vibration as shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Легирование железом частиц TiO 2 приводит к образо-ванию смешанных оксидов или смеси простых и смешан-ных оксидов [10]. Катионы железа Fe 3+ замещают Ti 4+ в катионных позициях, так как имеют близкие ионные ра-диусы Fe 3+ (0.64 ¦ ), Ti 4+ (0.610 ¦ ) и образуют твердые растворы с диоксидом титана при низких концентрациях железа (< 1%).…”
Section: Introductionunclassified